Nuclear and chloroplast genome diversity revealed by low-coverage whole-genome shotgun sequence in 44 Brassica oleracea breeding lines - Sampath Perumal; Nomar Espinosa Waminal; Jonghoon Lee; Hyun-Jin Koo; Boem-soon Choi; Jee Young Park; Kyounggu Ahn; Tae-Jin Yang (Horticultural Plant Journal, 2021)
Whole-genome shogun sequence (WGS) data generated by next-generation sequencing (NGS) platforms are a valuable resource for crop improvement. We produced 5–6 × WGS coverage of 44 Brassica oleracea breeding lines representing seven subspecies/morphotypes: cabbage, broccoli, cauliflower, kailan, kale, Brussels sprout, and kohlrabi to systematically evaluate the nuclear and chloroplast (Cp) diversity in the 44 B. oleracea breeding lines. We then exploited the impact of low-coverage NGS by evaluating nuclear genome diversity and assembly, annotation of complete chloroplast (Cp) genomes and 45S nuclear ribosomal DNA (45S nrDNA) sequences, and copy number variation for major repeats. Nuclear genome diversity analysis has revealed a total of 496 463 SNPs and 37 493 indels in the nuclear genome across the 44 accessions. Interestingly, some SNPs showed subspecies enrichment at certain chromosomal regions. The assembly of complete Cp genomes contained 153 361–153 372 bp with 37 variants including SNPs and indels. The 45S nrDNA transcription unit was 5 802 bp long with a total of 31 SNPs from the 44 lines. The phylogenetic tree inferred from the nuclear and Cp genomes coincided and clustered broccoli, cauliflower, and kailan in one group and cabbage, Brussels sprout, kale, and kohlrabi in another group. The morphotypes diverged during the last 0.17 million years. The Cp genome diversity reflected the unique cytoplasm of each subspecies, and revealed that the cytoplasm of many breeding lines was replaced and intermingled via inter-subspecies crosses during the breeding process instead. The polymorphic Cp markers provide a classification system for the cytoplasm types in B. oleracea. Furthermore, copy numbers of major transposable elements (TEs) showed high diversity among the 44 accessions, indicating that many TEs have become active recently. Overall, we demonstrated a comprehensive utilization of low-coverage NGS data and might shed light on the genetic diversity and evolution of diverse B. oleracea morphotypes.